Endothelial dysfunction and metabolic syndrome in preeclampsia: an alternative viewpoint. (April 2015) - Scioscia, Marco; Karumanchi, S. Ananth; Goldman-Wohl, Debra; Robillard, Pierre-Yves
Highlights: Immunological alterations promote endothelial dysfunction and metabolic syndrome. Endothelial dysfunction and insulin resistance characterize preeclampsia. Interpretation of intracellular mechanisms yields insight into the pathogenesis. Abstract: Several clinical and basic science reports have elucidated partial aspects of the pathophysiology of preeclampsia and have led many authors to conclude that different "subtypes" of the disease exist. All these subtypes share the main clinical features of the disease and present additional characteristics that define different clinical phenotypes. Nevertheless, immunological alterations, endothelial dysfunction, and insulin resistance constantly characterize this syndrome. These aspects are intimately related at a molecular level; thus, we propose an alternative approach to explaining biologically the main intracellular processes that occur in preeclampsia and this may yield an insight into the pathogenesis.